Pengaruh Human Relations, Reward, dan Punishment terhadap Peningkatan Kinerja Karyawan Pipa Baja PT Wijaya Prima Baja Indonesia - Sari, Ambar; Andriani , Dewi; Firdaus, Vera (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to determine how human relations variables, rewards, and punishments affect the performance improvement of steel pipe employees of PT Wijaya Prima Baja Indonesia. In this descriptive quantitative study, a random sampling method was used, with a sample size of 100 respondents. Distribution of questionnaires to collect data This study tested the validity, rehabilitation, normality, linearity, multicollinearity, autocorrelation, heteroscedasticity, multiple linear regression, t, f, and coefficient of determination (R2). The results of the human relations study showed that compensation improved employee performance, punishment improved employee performance, and rewards improved employee performance.